Rapid Growth in the CIS : Panel Regression Approach - Iradian, Garbis (IMF Working Papers; Working Paper ;, 2007)
This paper analytically explores and empirically tests a number of hypotheses to explain the rapid growth in transition economies. The paper finds that growth in the Commonwealth of Independent States (CIS) has been higher because of the recovery of lost output, progress in macroeconomic stabilization and market reforms, and favorable external conditions. Some of these factors are unlikely to continue for a very long time. The challenge is to improve the investment climate in the non-primary sectors, which will require broadening the scope of macroeconomic reform into a second generation of reforms encompassing structural and institutional areas.